Rare bird documentation form for Peregrine Falcon at Coralville Reservoir, 1983 - Newlon, Michael C.et al (1983)
Rare bird documentation form for a Peregrine Falcon at Ranch Corner at Coralville Reservoir in Johnson County, IA on October 2, 1983. Epson - sheet feed